2021
DOI: 10.1038/s41598-021-98276-2
|View full text |Cite
|
Sign up to set email alerts
|

Role of hypothalamic-pituitary adrenal-axis, toll-like receptors, and macrophage polarization in pre-atherosclerotic changes induced by social isolation stress in mice

Abstract: It has been well documented that chronic stress can induce atherosclerotic changes, however, the underlying mechanisms is yet to be established. In this regard, this study aimed to elucidate the relation between hypothalamic-pituitary adrenal-axis (HPA-axis), toll-like receptors (TLRs), as well as M1/M2 macrophage ratio and pre-atherosclerotic changes in social isolation stress (SIS) in mice. We used small interfering RNA against the glucocorticoid receptor (GR) to evaluate the relation between HPA-axis and TL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
2
2
0
Order By: Relevance
“…Our finding was consistent with those previous studies that the risks of AF, acute MI, hemorrhagic stroke, and heart failure were the highest immediately after the death of a child or a partner . The findings of a higher CVD risk shortly after sibling death may support the acute physiological mechanisms for posttraumatic stress on CVD, which included the activation of hypothalamic-pituitary-adrenal axis and short-term increased inflammatory activity . Additionally, our findings might support the roles of short-term lifestyle and behavior changes in the postbereavement period .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our finding was consistent with those previous studies that the risks of AF, acute MI, hemorrhagic stroke, and heart failure were the highest immediately after the death of a child or a partner . The findings of a higher CVD risk shortly after sibling death may support the acute physiological mechanisms for posttraumatic stress on CVD, which included the activation of hypothalamic-pituitary-adrenal axis and short-term increased inflammatory activity . Additionally, our findings might support the roles of short-term lifestyle and behavior changes in the postbereavement period .…”
Section: Discussionsupporting
confidence: 92%
“… 8 , 9 , 10 , 11 , 15 , 23 , 24 The findings of a higher CVD risk shortly after sibling death may support the acute physiological mechanisms for posttraumatic stress on CVD, which included the activation of hypothalamic-pituitary-adrenal axis and short-term increased inflammatory activity. 38 , 44 Additionally, our findings might support the roles of short-term lifestyle and behavior changes in the postbereavement period. 45 In contrast, a Swedish study of individuals born in 1932 to 1962 found a stronger association between sibling death and mortality in the longer term than in the short term, 30 and a Danish study from 1980 to 1996 only observed an increased risk of MI after 6 years of follow-up in parents who lost a child.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…This axis controls hormone synthesis and release, making it crucial for the ability to deal with adversity. Most individuals with depression have a hyperactive HPA axis (Haj-Mirzaian et al, 2021;Pariante & Lightman, 2008). Corticosteroids have been shown to affect emotional behaviors and cognition in animals and humans in a complex manner (Bos et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The activated sympathetic adrenal system can increase the number of immune response cells expressing M receptor and inflammatory cytokines [ 32 , 33 ] and produce a large number of cytokines. After HPA axis changes caused by chronic stress, TLR4/NF- κ B pathway activates proinflammatory cytokines such as MCP-1 and IL-1 α and IL-6 and, at the same time, leads to the increase of intimal macrophage/monocyte ratio [ 17 , 34 ], so that under the interaction of inflammatory factors and cells, endothelial homeostasis changes and inflammation further progresses and forms a vicious circle [ 35 ]. Interestingly, recent studies have also demonstrated that TLR4/NF- κ B pathway also downregulates HMGB1 protein-mediated PPAR γ /LXR α .…”
Section: Introductionmentioning
confidence: 99%